The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

The role and therapeutic potential of purinergic signaling pathway in metabolic syndrome-related atherosclerosis - Xiang Li; Chengxin Gong; Chengxiao Fu; Qing Xia; Yue Zhang; Yue Du; Yuting Sun; Hong Xu (Purinergic Signalling, 2026)

Developing a web-based participatory approach to model evaluation for environmental decision-making - Chengxin Qin; Fu Sun; Yi Rong; Wanbin Wang; Xingzi Zhang; Yihui Chen; Yi Liu (Environmental Modelling & Software, 2026)

Ca-based hybrid interfaces inhibit uncontrolled electrolyte decomposition for efficient Ion-Storage - Weihua Guo; Danchen Fu; Fei Tian; Huawei Song; Chengxin Wang (Chemical Engineering Journal, 2024)

Taking full advantage of ‘low-quality’ datasets in watershed modeling and management: From a perspective of parameter calibration - Yi Rong; Chengxin Qin; Haw Yen; Fu Sun; Pengfei Du; Siyu Zeng (Journal of Environmental Management, 2024)

Eliminating concentration polarization with gradient lithiophilic sites towards high performance lithium metal anodes under low N/P ratio - Zichun Xiao; Duzhao Han; Yu Fu; Keyu Xie; Wensheng Tian; Chengyong Shu; Kai Xi; Chengxin Peng; Yuping Wu; Shixue Dou; Wei Tang (Chemical Engineering Journal, 2024)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

Learning and inferring the diurnal variability of cyanobacterial blooms from high-frequency time-series satellite-based observations - Hu Li; Chengxin Qin; Weiqi He; Fu Sun; Pengfei Du (Harmful Algae, 2023)

Soil pH determines bacterial distribution and assembly processes in natural mountain forests of eastern China - Yingying Ni; Teng Yang; Yuying Ma; Kaoping Zhang; Pamela S. Soltis; Douglas E. Soltis; Jack A. Gilbert; Yunpeng Zhao; Chengxin Fu; Haiyan Chu (Global Ecology and Biogeography, 2021)
Aim There have been numerous studies of forest‐soil microbial biogeography, but an integrated view of edaphic factors, plant, climatic factors, and geographic distance in determining the variation of bacterial community and assembly processes remains unclear at large spatial scales. Here, we analysed the factors affecting the biogeographic pattern and assembly processes of soil bacterial communities under 58 tree species in five natural mountain forests. Location Eastern China. Major taxa studied Bacterial communities. Methods Hierarchical partitioning analysis and distance decay models were performed to evaluate the relative contributions of plant phylogeny, environmental, and spatial variables to the composition of bacterial communities. We applied the nearest taxon index (NTI), β‐nearest taxon index (βNTI), and the modified Raup–Crick metric to reveal the mechanisms of bacterial assembly processes. Results We found that plant phylogeny accounted for a significant, but minor, fraction (0.7%) of the variation in composition of bacterial communities. In contrast, soil pH was the primary determinant of bacterial diversity and community composition, independently explaining 68.6 and 69.9% of the variation, respectively. Based on the NTI analysis, bacterial community assembly was more phylogenetically clustered with increasing soil pH. Variable selection was the predominant process explaining bacterial community assembly when differences in soil pH were ≥ 0.83, whereas homogenizing dispersal dominated when differences in soil pH were Main conclusions Our findings provide strong evidence that soil pH predominantly determines bacterial distribution and mediates the relative impact of stochasticity and determinism in soil bacterial community assembly. This suggests that climate‐change associated forest soil acidification could have a dramatic impact on soil bacterial diversity, composition, and function.

Verification of soman-related nerve agents via detection of phosphonylated adducts from rabbit albumin in vitro and in vivo - Feiyan Fu; Runli Gao; Ruihua Zhang; Pengcheng Zhao; Xiaogang Lu; Liqin Li; Hongmei Wang; Chengxin Pei (Archives of Toxicology, 2019)

Characterization of the complete chloroplast genome of Gymnocarpos przewalskii, an endangered species in China and Mongolia - Zhaoping Yang; Yunyan Zhang; Li Pan; Chengxin Fu (Conservation Genetics Resources, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

An efficient regeneration system via direct and indirect organogenesis for the medicinal plant Dysosma versipellis (Hance) M. Cheng and its potential as a podophyllotoxin source - Weimei Jiang; Luxi Chen; Qi Pan; Yingxiong Qiu; Yingying Shen; Chengxin Fu (Acta Physiologiae Plantarum, 2012)

Relationships and Hybridization among Smilax china and Its Affinities: Evidence from Allozyme Data - Aili Wang; Yeye Chen; Guangchun Chen; Joongku Lee; Chengxin Fu (Biochemical Genetics, 2008)

Phylogenetic Relationships and Possible Hybrid Origin of Lycoris Species (Amaryllidaceae) Revealed by ITS Sequences - Shude Shi; Yingxiong Qiu; Enxiang Li; Ling Wu; Chengxin Fu (Biochemical Genetics, 2006)